2005
DOI: 10.1136/bjo.2005.067298
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the test-retest variability of Heidelberg retina tomograph and Heidelberg retina tomograph II measurements

Abstract: Aims: To evaluate the test-retest variability of stereometric parameter measurements made with the Heidelberg retina tomograph (HRT) and Heidelberg retina tomograph-II (HRT-II), and to establish which parameter(s) provided the most repeatable and reliable measurements with both devices. An investigation into the factors affecting the repeatability of the measurements of this parameter(s) was conducted. Methods: 43 ocular hypertensive and 31 glaucoma subjects were recruited to a test-retest study. One eye from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 27 publications
8
105
1
6
Order By: Relevance
“…13,[24][25][26] Although different stereometric parameters have been suggested as useful markers of progression, some studies have suggested that the neuroretinal rim area (RA) is the most reliable and reproducible measure for detection of change. 27,28 Changes in RA have been demonstrated in glaucoma patients followed over time and are associated with disease progression. 14,15,22,[28][29][30][31][32][33][34] Baseline measurements obtained by the HRT have also been shown to predict future conversion to glaucoma in patients suspected of having the disease, although the predictive accuracy of the measurements on individual patients is generally low.…”
Section: Cslomentioning
confidence: 99%
“…13,[24][25][26] Although different stereometric parameters have been suggested as useful markers of progression, some studies have suggested that the neuroretinal rim area (RA) is the most reliable and reproducible measure for detection of change. 27,28 Changes in RA have been demonstrated in glaucoma patients followed over time and are associated with disease progression. 14,15,22,[28][29][30][31][32][33][34] Baseline measurements obtained by the HRT have also been shown to predict future conversion to glaucoma in patients suspected of having the disease, although the predictive accuracy of the measurements on individual patients is generally low.…”
Section: Cslomentioning
confidence: 99%
“…The factors evaluated were age, intraocular pressure (IOP), CCT, disc area and vertical cup-to-disc ratio. As rim area represents a more clinically meaningful measure and was used in previous studies to assess factors associated with testretest measurement variability (9) , we used this HRT parameter (expressed by the rim area CVw) as the dependent variable in our analysis. All statistical analyses were performed using Medcalc version 7.4.2.0 (Medcalc Software, Mariakerke, Belgium).…”
Section: Discussionmentioning
confidence: 99%
“…Although it provides useful information that helps the physician to distinguish between progressing and non-progressing patients, Heidelberg Retina Tomograph (HRT) images are not identically scaled versions of the true ONH and are affected by measurement variability during image acquisition (intra-scan noise) and between visits during follow-up (inter-scan noise) (6) . Although previous studies have found good reproducibility for HRT topographic measurements, most of these studies used previous versions of the HRT and only a few assessed potential sources of measurement variability (7)(8)(9)(10)(11) . It is well known that a device reproducibility is critical for following glaucoma patients over time.…”
Section: Introductionmentioning
confidence: 99%
“…Lan et al have reported that HRT defined-rim area has a good correlation to HVF MD for glaucoma diagnosis [14]. Strouthidis et al using both the HRT classic and the HRT2 have suggested that rim area is a useful tool for assessing disease progression with good correlation between the two versions of the same instrument [15]. Fayers and coauthors have also proposed an event based analysis of sectorial rim area adjusted for image quality and number of observations for the monitoring of glaucoma progression [16], Zangwill et al have suggested that the MRA (which adjusts rim area to disc size) is a useful biomarker for glaucoma diagnosis [17].…”
Section: Hrt Evidence Of Damagementioning
confidence: 99%
“…The discrepancy with the literature could be due to the use of different imaging techniques for ONH assessment and on different study populations. Nevertheless, rim area, by itself or incorporated in the MRA, is one of the most frequently used parameters for glaucoma diagnosis and follow-up [14][15][16][17]. Lan et al have reported that HRT defined-rim area has a good correlation to HVF MD for glaucoma diagnosis [14].…”
Section: Hrt Evidence Of Damagementioning
confidence: 99%